INTERNET CONSUMPTION IN A NEW HOME - Cui, Shuang (My University, 2013)
Through an interpretative lens, the current study examined how international students’ Internet use affects their new lives in the host country. Eight Chinese graduate students participated in this study. The data was collected through face-to-face qualitative in-depth interviews, which were guided by a semi-structured interview guide using open-ended questions. It was found that the Internet plays a significant role in the development of these students’ social capital in a new country. International students use internet to maintain the newly-built social relations in Canada and the old ones in China. Through the Internet, the students can get informational and emotional supports, which are essential in the acculturation process. It was also indicated that the Internet is a transnational space where these students can manage the complex interactions of differing cultural values and norms between China and Canada without synthesizing differences. The findings of this study are expected to make contributions to the knowledge of the experiences and support needs of International students on campus. Recommendations for school programs and policies are outlined.
Keywords: international students; social capital; internet; Social Work; Social Work